Environmental rearing effects on impulsivity and reward sensitivity - Kirkpatrick, Kimberly; Marshall, Andrew T.; Clarke, Jacob; Cain, Mary E. (My University, 2013)
Previous research has indicated that rearing in an enriched environment may promote self-control in an impulsive choice task. To further assess the effects of rearing environment on impulsivity, two experiments examined locomotor activity, impulsive action, impulsive choice, and different aspects of reward sensitivity and discrimination. In Experiment 1, rats reared in isolated or enriched conditions were tested on an impulsive choice procedure with a smaller-sooner versus a larger-later reward, revealing that the isolated rats valued the smaller-sooner reward more than the enriched rats. A subsequent reward challenge was presented in which the delay to the two rewards was the same but the magnitude difference remained. The enriched rats did not choose the larger reward as often as the isolated rats, reflecting poorer reward discrimination. Impulsive action was assessed using a differential-reinforcement-of-low-rate task, which revealed deficits in the enriched rats. In Experiment 2, rats reared in isolated, standard, or enriched conditions were tested on reward contrast and reward magnitude sensitivity procedures. The rats were presented with two levers that delivered different magnitudes of food on variable interval 30-s schedules. Across all tests, the enriched and social rats displayed more generalized responding to the smaller-reward lever, but a similar response to the large-reward lever, compared to the isolated rats. This confirmed the results of Experiment 1, indicating poorer reward discrimination in the enriched condition compared to the isolated condition. The results suggest that enrichment may moderate reward generalization/discrimination processes through alterations in incentive motivational processes.
Keywords: Environmental enrichment; Isolation rearing; Impulsive choice; Impulsive action; Reward processing